(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Black money’s presence in the social, economic, and political spheres of our lives is well documented to have a detrimental impact on how the nation’s institutions and public policies are run. The poor are disproportionately impacted by systemic corruption and failed governance. All of the country’s problems stem from black money, and many frauds utilising public property are an expression of this. Finding the connection between the new economic strategy and black money is essential, and appropriate action must be done. One of the major difficulties when it comes to a nation like India is black money, which is a huge problem in many nations. This problem is not a recent one for India; rather, it is a problem that has existed for a very long time. One must comprehend this issue’s true meaning in order to grasp its essence. Black money is defined as "money earned through any illegal activity regulated by the laws of the country." This type of money is typically earned in cash through a variety of activities without being declared to the government for tax purposes. Black money was first used in the early 20th century. After the nation evolved, namely after independence, black money came to light. However, in current times, black money has become a key issue in determining new economic activity, shaping national policies, and occasionally determining the law of the land.